Factors associated with diagnostic delay in recurrent TB - Zhongyao Xie; Tingwei Wang; Hongguang Chen; Donglin Wang; Xiangqi Gao; Yi Hui (BMC, 2020)
Abstract Background Recurrent tuberculosis (TB) contributes to the burden of TB. The study was designed to explore the time of diagnostic delay and risk of delay in patients with recurrent TB in China. Methods A total of 13,334 patients with new and recurrent TB registered in Yulin a city in China were included. The Kaplan-Meier survival curve was employed to estimate the median delay time. The mixed-effects survival model was used to identify the correlates associated with diagnostic delay. The outcome of interest in the model was"being diagnosed". Results We found that 6.5% of cases with TB were attributed to recurrence. The median delay time of recurrent TB cases (73 days) was more than twice as long as that of new TB (35 days). Individuals with recurrent TB had a higher risk of diagnostic delay than new TB (HR, 0.5, 95%CI, 0.5-0.6). Factors associated with diagnostic delay differed between new TB and recurrent TB cases. Immigrants (HR, 0.5, 95%CI, 0.3-0.9), cases notified by way of recommendation (HR, 0.6, 95%CI, 0.4-0.9) and diagnosed at TB dispensary (HR, 0.4, 95%CI, 0.3-0.6) were associated with a higher risk of a longer delay for recurrent TB cases. Conclusions The proportion of TB cases attributed to recurrence was high. Patients with recurrent TB had a longer delay time and a higher risk of diagnostic delay. Further interventions to improve diagnostic delay should focus on screening for TB in immigrants, improving public health services at the lowest healthcare level and update of TB diagnosis and management model.